The Behavior of Polymer RC Columns Exposed to aggressive Soils - Rasheed, L Sh; Salih, Sh A; Hanash, Z F (IOP conference series. Materials Science and Engineering, 2020)
One of the most important properties about the durability of concrete is its resistance to sulfate attack. In this search, the effect of sulfate salts on reinforced polymer concrete columns was studied, the columns buried in two types of soil, sand and clay, in depth of 3 m, in one of the agricultural areas in the holy city of Karbala. The sandy soil comprised 10.609% of SO3, the clay soil 2.61%SO3. A compressive test for reinforced concrete columns, compressive test for concrete cubes and a tensile splitting test for concrete cylinders were applied, absorption, voids ratio and density also measured. A ratio of polymer / cement = 7.5% was found to reduce the compressive strength of polymer reinforced concrete columns buried in clay soil at ages 60, 150 and 240 days by 23.97, 20.28 and 24.96%. When buried in sandy soil, the decrease in strength was 31.12, 20.03 and 37.52 % respectively, in comparison to the reference column. From this it can be concluded that the use of a polymer (SBR) has negatively affected the strength of reinforced concrete columns after 150 days so is not recommended for use in concrete facilities which are subject to attack by sulfate salts.